PENGOLAHAN PANGAN BERBAHAN BAKU UBI JALAR SEBAGAI UPAYA PENINGKATAN EKONOMI KELUARGA - Prastiwi, Wahyu Dyah; Dalmiyatun, Tutik; Muhammad, Alaya F.H. (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2017)
This study described the implementation of applicable technology in woman farmer's group in Mendongan Village, Sumowono, Semarang Regency. The program is aimed to share knowledge of sweet potatoes processing in order to increase the family income of the group. Counseling and baking class is conducted to gain the participation and skill of the group member. A sweet potato cutter machine is made to improve the activities and performance of the group. The program is succeeded and gave benefit to the group.